PROFESIONALITAS GURU PAI DI SMAN 2 SEMARANG - Agustina, Lina (Universitas Islam Sultan Agung, 2018)
In this study, the problem that arises is how the Islamic Education Teacher Professionalism associated with the 4 competencies of teachers and Teacher Academic Qualification as listed in the laws. How can a teacher be able to develop the four competencies required of qualified academic and inline with the subjects of teaching. The extent to which a teacher was able to carry out the responsibilities and duties - duties properly. Not only the responsibility for learning in the classroom but how learners are able to actualize in daily life - today. The informants of this study was teacher of Islamic education at the Senior High School 2 Semarang and learners in the school environment. Research on the professionalism of teachers of Islamic education in the National High School 2 Semarang, using the technique of collecting data through interviews, observation and documentation. The analysis model used in this study is komponensial domain analysis. The results obtained show that , as a professional educator should not only academically , but personality and way of socializing with the environment is also become very important. Moreover, a teacher with a good personality and social will be a lot of good influence to the learners. Because teachers with personal and social wellcapable of being role models for their students.